Physicochemical phenomena leading to slip of a fluid along a solid surface. (March 2019) - Malkin, Alexander Ya.; Patlazhan, Stanislav A.; Kulichikhin, Valerii G.
Abstract : The aim of the review is to analyze theoretical approaches to the explanation of the phenomenon of slip of different media including homogeneous fluids and multicomponent systems, such as pastes, microgels, concentrated suspensions, highly concentrated emulsions and polymer melts along solid walls. The wall slip conditions and physical mechanisms are considered. The influence of molecular interactions of homogeneous fluids and disperse systems with hydrophobic and hydrophilic solid surfaces, as well as the role of surface roughness, nanobubbles, deformation-induced relaxation transition from liquid to solid-like behaviour of viscoelastic polymers in the course of slip are demonstrated. Key results of experimental studies are discussed. The bibliography includes 296 references.